Military's Strangest Campaigns & Characters: Extraordinary But True Stories - Tom Quinn
A completely circular Russian warship, a pantsless colonel$1 (Bthis compendium examines some of the most remarkable campaigns, incidents, and characters from the earliest recorded histories to the second Gulf war These strange but true stories include figures both famous and obscure, from Wellington, Churchill, and Napoleon to maverick soldier "Popski" Peniakoff, who commanded a company of British soldiers in North Africa during World War II. Known as "Popski's Private Army," this motley bunch were highly unorthodox but very effective in raiding Axis supply columns and destroying Luftwaffe aircraft. Then there's the unusual Russian warship Novgorod , which was completely circular, and the Victoria Cross winner who survived completely unscathed against all odds; not to mention the old colonel who went into battle with his trousers down and the woman who fought as a man for nearly 20 years without being discovered . Making for bizarre yet absorbing reading, this history highlights the origins of strange regimental traditions, heroic and ridiculous soldiering, and the folly of commanding officers throughout the ages.s